Perbandingan Konsentrasi HPMC Terhadap Stabilitas Fisik Sediaan Gel Ekstrak Etanol Daun Sirsak (Annona Muricata L.) - Any Khoirotuzzahra; Fajaryanti, Nita; Esti Mediastini; Pitarisa, Agustina Putri (Journal Clinical Pharmacy and Pharmaceutical Science, 2025)
The soursop leaves (Annona muricata L.) are one of the plants containing acetogenins compounds and some alkaloids muricolin, cauxine, couclamine, stepharine and reticulin. These compounds are able to act as antibacterial causes of acne namely Propionibacterium acnes and Staphylococcus aureus. The extraction of soursop leaves is obtained by extracting the leaves of the shingle using the maseration method. The extract is formulated into a gel set with a difference in HPMC base concentration(Hydroxy Propyl Methyl Cellulose). The use of different HPMC concentrations aims to know the base concentration of HPMC there are differences or not in the gel ready ethanol extract of the shingle leaves. Physical stability testing conducted includes organoleptic, homogeneity, protection power, scatter power, lystuff, pH and viscosity with storage room temperature of 25ºC - 30ºC for 4 weeks. The results of the gel-ready physical stability study at room temperature storage of 25ºC - 30ºC for 4 weeks showed stable results for organoleptic testing, homogeneity, protection power, scattering power, pH and 2% thness at HPMC concentrations, while unstable results in viscosity tests.